2007
DOI: 10.1002/gps.1890
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antidepressant use in depressed and non‐depressed community‐dwelling elderly: the three‐city study

Abstract: This study showed that the direction and strength of the association between antidepressant use and demographic and health-related factors varied according to the severity of depression symptoms. Further studies are needed to clarify the relationship between gender and cognition and antidepressant use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“… 1 , 13 Another cause would be extended drug treatment for depression, particularly among those with a history of multiple depressive episodes. This has also been observed in international studies, whether based on primary data 14 , 21 , 22 or on databases of consultations and medical prescriptions. 18 A third cause is growing acceptance among healthcare professionals and patients of the new generation of AD such as SSRI, which have fewer side effects and are better tolerated and safer than TCA and MAOI (older class), particularly in overdose situations.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“… 1 , 13 Another cause would be extended drug treatment for depression, particularly among those with a history of multiple depressive episodes. This has also been observed in international studies, whether based on primary data 14 , 21 , 22 or on databases of consultations and medical prescriptions. 18 A third cause is growing acceptance among healthcare professionals and patients of the new generation of AD such as SSRI, which have fewer side effects and are better tolerated and safer than TCA and MAOI (older class), particularly in overdose situations.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence of SSRI among AD used by the 2012 cohort is consistent with that observed in Brazil 6 , 19 and other countries. 22 This result indicates the possibility that among the older people of Bambuí, increased consumption of AD results from greater acceptance of SSRI by professionals and patients. After the appearance of this chemical subgroup, general practitioners have more frequently prescribed AD, a practice that used to be restricted to psychiatrists.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies (from the US) reported no statistical association between education and antidepressant use (Blazer et al, 2000;Grunebaum et al, 2008). Similarly, most previous studies that have investigated the association between income and antidepressant association have found no significant relationship (Blazer et al, 2000;Grunebaum et al, 2008;Soudry et al, 2008), with the results of another study suggesting that people with higher levels of income were more likely to use antidepressants (Brown et al, 1995). A possible reason for discrepancy between our results and those from other countries is that, because the concessional PBS benefits are available to low-income earners, access to medications in this subset of the Australian population may not be as tied to the ability to pay as in other countries.…”
Section: Results Of the Study In Relation To Other Studiesmentioning
confidence: 92%
“…When medical visits are more frequent, patients can receive more thorough information about their treatment, its mode of action, and the need for monitoring and managing adverse events so that they pursue it (Bull et al, 2002). This better compliance might also be due to greater concern for their health and closer following of advice provided by healthcare professionals in the population aged 75 years and over (Soudry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%